Collagen COL22A1 maintains vascular stability and mutations in COL22A1 are potentially associated with intracranial aneurysms - Ton, Quynh V. (Dis Model Mech, 2018)
Collagen XXII (COL22A1) is a quantitatively minor collagen, which belongs to the family of fibril-associated collagens with interrupted triple helices. Its biological function has been poorly understood. Here, we used a genome-editing approach to generate a loss-of-function mutant in zebrafish col22a1. Homozygous mutant adults exhibit increased incidence of intracranial hemorrhages, which become more prominent with age and after cardiovascular stress. Homozygous col22a1 mutant embryos show higher sensitivity to cardiovascular stress and increased vascular permeability, resulting in a greater percentage of embryos with intracranial hemorrhages. Mutant embryos also exhibit dilations and irregular structure of cranial vessels. To test whether COL22A1 is associated with vascular disease in humans, we analyzed data from a previous study that performed whole-exome sequencing of 45 individuals from seven families with intracranial aneurysms. The rs142175725 single-nucleotide polymorphism was identified, which segregated with the phenotype in all four affected individuals in one of the families, and affects a highly conserved E736 residue in COL22A1 protein, resulting in E736D substitution. Overexpression of human wild-type COL22A1, but not the E736D variant, partially rescued the col22a1 loss-of-function mutant phenotype in zebrafish embryos. Our data further suggest that the E736D mutation interferes with COL22A1 protein secretion, potentially leading to endoplasmic reticulum stress. Altogether, these results argue that COL22A1 is required to maintain vascular integrity. These data further suggest that mutations in COL22A1 could be one of the risk factors for intracranial aneurysms in humans.